Paediatric Eye Care in Nepal - Adhikari, Srijana (Nepalese Journal of Ophthalmology, 2025)
Visual development is an important aspect of infant and child development. Vision is a complex sensorineural process, the development of which begins soon after the birth. Healthy eyes and good vision are key components to achieve many important developmental milestones in children. Hence Paediatric eye care should be started as soon as the child is born and continue throughout childhood and adolescence. It is an important public health component as childhood blindness carries a lifetime of economical and psychosocial impact.